2018
DOI: 10.1038/pr.2017.330
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of reintubation in extremely preterm infants: a longitudinal cohort study

Abstract: BackgroundThe optimal approach for reporting reintubation rates in extremely preterm infants is unknown. This study aims to longitudinally describe patterns of reintubation in this population over a broad range of observation windows following extubation.MethodsTiming and reasons for reintubation following a first planned extubation were collected from infants with birth weight ≤1,250 g. An algorithm was generated to discriminate between reintubations attributable to respiratory and non-respiratory causes. Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 18 publications
2
53
2
1
Order By: Relevance
“…Strengths of this study include the relatively large number of subjects, bootstrapping techniques to obtain confidence intervals, and the similarity of their cohort's extubation success and definitions to other previous studies on this topic. The time window selected for inclusion of reintubation attempts is consistent with other reports that majority of respiratory related reintubations occur within 7 days of extubation [9]. The addition of an online calculator offers the potential for bedside applicability of these findings.…”
supporting
confidence: 71%
“…Strengths of this study include the relatively large number of subjects, bootstrapping techniques to obtain confidence intervals, and the similarity of their cohort's extubation success and definitions to other previous studies on this topic. The time window selected for inclusion of reintubation attempts is consistent with other reports that majority of respiratory related reintubations occur within 7 days of extubation [9]. The addition of an online calculator offers the potential for bedside applicability of these findings.…”
supporting
confidence: 71%
“…Prevention of reintubation of preterm infants holds significant promise in improving overall outcomes of this fragile population. Cohort studies have reported that almost half of infants with birth weights less than 1500 g and almost two-thirds of infants with birth weights less than 1000 g require at least one reintubation for resumption of invasive positive pressure ventilation during the NICU stay [24][25][26]. The time interval between an extubation and resumption of mechanical ventilation has been reported to range from hours to days [24].…”
Section: Discussionmentioning
confidence: 99%
“…Baseline patient demographics (BW, gestational age, sex, APGAR scores, and weight, postnatal age and post‐menstrual age at extubation), pre‐extubation blood gas (pH, partial pressure of CO 2 , bicarbonate, base excess), ventilator settings (ventilation mode, peak inflation pressure (PIP), positive end‐expiratory pressure (PEEP), mean airway pressure (MAP), FiO 2 , and inflation rate), post‐study non‐invasive respiratory support (mode, PIP, PEEP, and inflation rates) and extubation outcomes were prospectively collected. Extubation failure was defined as the need for reintubation within 7 days from extubation . The primary reason for reintubation was also recorded.…”
Section: Methodsmentioning
confidence: 99%